Impact of Noise-Attenuating Headphones on Participation in the Home, Community, and School for Children with Autism Spectrum Disorder. (2nd January 2019) - Pfeiffer, Beth; Erb, Shelly Raee; Slugg, Laura
Abstract: Aim : The purpose of this study was to conceptualize the benefits and limitations of using noise-attenuating headphones for children with autism spectrum disorder (ASD) on participation in home, community, and school environments from the perspective of parents and teachers. Methods : Grounded theory methodology was used to guide data collection and analysis. Ten parents and five teachers of children with ASD and auditory hypersensitivity aged 6–12 completed recorded interviews. Interviews were transcribed and crosschecked prior to analysis by two or more researchers. Constant comparison was used during open and axial coding followed by theoretical integration. Results : Participants identified that the use of noise-attenuating headphones increased participation in home, community, and school settings. Barriers and benefits were identified for both around-ear and in-ear headphones. Preparation for use was an identified strategy that reduced the barriers and increased use of the headphones. Additionally, many of the children learned to predict when they needed the headphones and requested their use. Conclusion : Results of the study identified parental and teacher support for the use of noise-attenuating headphones to increase participation in natural environments for children with ASD, as well as suggestions to facilitate use for practicing physical and occupational therapists.